Manifestation of the Jahn-Teller eﬀect subject to quadratic T ⊗ (e + t2) problem in ultrasonic attenuation. Case study of CaF2:Cr crystal with isovalent and aliovalent substitution - Sarychev, Maksim N; Hosseny, Wessam A L; Zhevstovskikh, Irina Vladimirovna; Ulanov, Vladimir A; Shakurov, Gilman S; Egranov, Aleksandr V; Surikov, Vladimir T; Averkiev, Nikita; Gudkov, Vladimir (Journal of physics. Condensed matter, 2022)
A new approach is introduced to obtain information about the adiabatic potential energy surface of the Jahn-Teller complexes subject to the T ⊗ (e + t2) problem in doped crystals. It employs simulation of the contribution of the Jahn-Teller sub-system to ultrasonic attenuation with account of three mechanisms of relaxation and subsequent comparison with the experimental data on temperature dependence of the attenuation obtained with the use of doped crystal and nominally pure one. The approach has been applied to the CaF2 crystal doped with chromium. The experiment has been carried out at the frequencies of (13 - 158) MHz at low temperatures (4 - 170 K). Peak for all the ultrasonic normal modes propagating along the [110] axis has been observed at about 8 K.. It has been considered as the Jahn-Teller eﬀect manifestation by the sub-system of Cr2+F8 complexes. Symmetry properties of the global minima and saddle points have been identiﬁed, the Jahn-Teller stabilization energies and coordinates of the extrema points in the ﬁve-dimensional space of symmetrized displacements have been evaluated. Besides, a broad shoulder has been found at 15 - 40 K and attributed to contribution of the Cr3+F8 sub-system.